The economist's oath : on the need for and content of professional economic ethics - DeMartino, George (Oxford : Oxford University Press, 2011)
'The Economist's Oath' seeks to initiate a serious conversation among economists about the ethical content of their work, by raising fundamental questions on the nature of what economists do and how ethics can and should be involved in this.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Economics -- Moral and ethical aspects; Business ethics; Social ethics